The efficacy of combined music therapy and Tai Chi for major depressive disorder: Study protocol for a randomized controlled trial. Issue 12 (26th March 2021) - Xie, Huixian; Tang, Yiping; Cheng, Fengmin; Chu, Jucai
Abstract: Background: There are no clinical trials evaluating the efficacy of combined music and Tai Chi therapy for patients with major depression. Therefore, the primary objective of the present study was to evaluate the efficacy of Tai Chi and music therapy on psychological status and quality of life among patients with major depressive disorder in China. Methods: This work is a part of a comprehensive research project to assess and provide intervention that potentially improves psychological status and quality of life among patients with major depressive disorder. This research project has been received ethical approval from the Medical Research and Ethics Committee in Taizhou Second People's Hospital (no. tzey2020023). After the introductory briefing, the acceptance to take the presession questionnaire implied the participant's consent to participate in the study. Eligible participants are divided into 3 groups according to completely randomized design: combined group (music therapy + Tai Chi), music therapy alone group, and Tai Chi alone group. The analyses will be performed using SPSS 22.0.0 (SPSS Inc, Chicago, IL). Results: This protocol will provide a reliable theoretical basis for the following research. Conclusion: The sample came from a single health center. Therefore, the results cannot be generalized for the entire population. Trial registration: This study protocol was registered in Research Registry (researchregistry6597).